The Influence of Teaching Style and Motor Ability Level Toward Pencak Silat Learning Results on The Fifth Grade Students of SD Hj Isriati Baiturrahman 2 Semarang City - Saputra, Visi Dwi; Sugiharto, Sugiharto; Soekardi, Soekardi (Journal of Physical Education and Sports, 2018)
The purpose of this research is to know and analyze: (1) the difference of guided discovery teaching style’s influence with part and whole method approach assisted by visual media toward pencak silat learning results, (2) the difference of high and low motor ability level’s influence toward pencak silat learning results, and (3) interaction between teaching style and motor ability level toward pencak silat learning style. This research used experimental method in 2x2 factorial design. The sampling technique is by purposive sampling technique and the sample was 48 students from the total population of 152 students. Data analysis techniques in this research used two way analysis of variance (ANOVA) in significance level α = 0.05. Conclusions (1) the learning results of pencak silat between the students who taught by using guided discovery teaching style with whole method approach assisted by visual media were better than the students who taught by using guided discovery teaching style with whole method approach assisted by visual media, (2) pencak silat learning results of the students who had high motor ability level were better than by using guided discovery teaching style with whole method approach assisted by visual media the students who had low motor ability level, and (3) there was interaction between teaching style and motor ability toward pencak silat learning results. It is suggested to used teaching style variation of guided discovery with whole method approach which is aided by visual media on the physical learning in term of pencak silat material.